2012
DOI: 10.1161/atvbaha.111.238329
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Role of CD40 Signaling in Vascular Wall Cells in Neointimal Formation and Vascular Remodeling After Vascular Interventions

Abstract: Objective It has been shown that CD40-TRAF6 axis in leukocytes plays a significant role in neointimal formation after carotid ligation. Because CD40 and TRAF6 are expressed not only in leukocytes but also in vascular cells, we examined the role of CD40 contributed by vascular wall cells in neointimal formation after carotid ligation in an atherogenic environment. Methods and Results Both CD40 and TRAF6 in medial smooth muscle cells (SMCs) was upregulated significantly at 3 d and more prominently at 7 d after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 58 publications
1
48
0
3
Order By: Relevance
“…37 In addition, both in vivo and in vitro data showed that TRAF6 deficiency prevented injury-induced SMC apoptosis but did not affect SMC proliferation and migration. 38 These findings suggest that TRAF6 might be a negative regulator of VSMC survival and vascular remodeling. However, another study found that TRAF6 silencing inhibited interleukin-1β-induced angiogenesis in mice in vivo, 39 implying a protective role of TRAF6 in vascular cell survival.…”
Section: Discussionmentioning
confidence: 92%
“…37 In addition, both in vivo and in vitro data showed that TRAF6 deficiency prevented injury-induced SMC apoptosis but did not affect SMC proliferation and migration. 38 These findings suggest that TRAF6 might be a negative regulator of VSMC survival and vascular remodeling. However, another study found that TRAF6 silencing inhibited interleukin-1β-induced angiogenesis in mice in vivo, 39 implying a protective role of TRAF6 in vascular cell survival.…”
Section: Discussionmentioning
confidence: 92%
“…Our laboratory has focused on investigating the role of CD40L/CD40 in the vascular response to injury. We have demonstrated that either antibody blockade of CD40L or genetic deletion of its receptor CD40 reduces early leukocyte (neutrophil and monocyte) accumulation in the injured arteries and limits eventual neointima formation after vascular injury in mice [16], [19], [32]. Nevertheless, the exact involvement of CD40L/CD40 in neutrophil recruitment and function remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…NF-kB p65 nuclear translocation in neutrophils was examined by immunocytochemical method, as previously described [19]. Briefly, freshly isolated neutrophils (from WT, CD40 −/− , and Mac-1 −/− mice) were resuspended in RPMI 1640 containing 0.5% (w/v) low-endotoxin BSA.…”
Section: Methodsmentioning
confidence: 99%
“…CD154 is expressed by a variety of immune and non-immune cells: apart from activated T-cells, activated platelets express CD154 at their surface and release soluble CD154 (sCD154); platelets represent a primary reservoir of CD154 and source of circulating sCD154 in the organism [Henn et al, 1998;Andre et al, 2002;Viallard et al, 2002]. CD154 may contribute to the regulation of matrix remodeling proteins, particularly through the induction of MMP-9 [Schonbeck et al, 1997;Mach et al, 1999;Li et al, 2008;Song et al, 2012;Bou Khzam et al, 2013].We hypothesized that the control of the production of matrix remodeling proteins by podocytes upon exposure to CD154 may contribute to GBM homeostasis. We therefore studied the expression of CD40 by podocytes and the involvement of CD40/ CD154 signalization in the regulation of MMP-9 expression in podocytes.…”
mentioning
confidence: 99%